2016
DOI: 10.3389/fpls.2016.01481
|View full text |Cite
|
Sign up to set email alerts
|

Suitable Reference Genes for Accurate Gene Expression Analysis in Parsley (Petroselinum crispum) for Abiotic Stresses and Hormone Stimuli

Abstract: Parsley, one of the most important vegetables in the Apiaceae family, is widely used in the food, medicinal, and cosmetic industries. Recent studies on parsley mainly focus on its chemical composition, and further research involving the analysis of the plant's gene functions and expressions is required. qPCR is a powerful method for detecting very low quantities of target transcript levels and is widely used to study gene expression. To ensure the accuracy of results, a suitable reference gene is necessary for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 53 publications
5
27
0
Order By: Relevance
“…The four computational methods (ΔCt, BestKeeper, NormFinder and geNorm) (Niu L. et al, 2015 ; He et al, 2016 ; Li et al, 2016a ) for expression stability are based on different algorithms and analytical procedures (Vandesompele et al, 2002 ; Andersen et al, 2004 ; Pfaffl et al, 2004 ; Silver et al, 2006 ). In our research, we found that the most unstable genes identified by the four algorithms were mostly the same, but the most stable genes were not consistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The four computational methods (ΔCt, BestKeeper, NormFinder and geNorm) (Niu L. et al, 2015 ; He et al, 2016 ; Li et al, 2016a ) for expression stability are based on different algorithms and analytical procedures (Vandesompele et al, 2002 ; Andersen et al, 2004 ; Pfaffl et al, 2004 ; Silver et al, 2006 ). In our research, we found that the most unstable genes identified by the four algorithms were mostly the same, but the most stable genes were not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…This was possibly due to differences among the algorithms. Integrated analysis using different programs can minimize errors in the stability evaluation of candidate reference genes (Li et al, 2016a ; Shivhare and Lata, 2016 ). Here, RefFinder (Xie et al, 2012 ) was used to combine the results of the four computational methods and generate a comprehensive ranking list for the candidate reference genes.…”
Section: Discussionmentioning
confidence: 99%
“…Three different Microsoft Excel-based software programs, geNorm [3], NormFinder [15], and BestKeeper [13,34], were used to analyze the expression stability of the candidate RGs under different experimental conditions. The Cq (PCR cycle threshold) data were used directly in the BestKeeper program, but for geNorm and NormFinder, Cq values were converted into relative values and imported into geNorm and NormFinder program analyzed as described previously [13]. The output of each software program permitted us to rank the expression stability of RGs in different treatment groups.…”
Section: Gene Expression Stability Analysismentioning
confidence: 99%
“…Unlike the other two programs, BestKeeper ranks RGs based on the standard deviation (SD) and coefficient of variation (CV) of the Cq values from the qRT-PCR assay. The smaller the CV, the better the stability of the gene was [13,34]. The results of BestKeeper analysis are also listed in Table 5.…”
Section: Gene Stability Gene Stability Gene Stability Gene Stability mentioning
confidence: 99%
“…An ideal internal reference gene should have the following characteristics: (1) stable expression in different tissues and developmental stages, and not affected by experimental treatment; (2) cannot be a pseudogenes; (3) The expression level should be in a suitable range (15 < Cq < 30), not too low or too high [22,29]. ACTIN, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), elongation factor 1alpha (EF1α), and ubiquitin-conjugating enzyme (UBC) are commonly used internal reference genes in plant gene expression analysis experiments [17].…”
mentioning
confidence: 99%